Fixed-dose combination antituberculosis therapy as a risk factor for tuberculosis recurrence: an evidence-based case report - Arvin Pramudita; Cleopas M Rumende; Ardi Findyartini (Acta Medica Indonesiana)
Background: a patient with a history of tuberculosis (TB) has a risk up to 27% to develop recurrence within 2 years after being cured. Indonesia itself has more than 7,500 recurrent cases annually, regardless of reinfection or relapse. This is an important problem, as recurrent TB is associated with lower cure rates with the anti-TB therapy and higher risk of developing drug resistance. Some risk factors for this recurrence are smoking, poor treatment adherence, low economic status, and weak immune status. This study is aimed to identify whether the use of fixed-dose combination (FDC) anti-tuberculosis therapy increases the risk for tuberculosis recurrence compared with using separate drug formulation. Methods: the search was conducted on MEDLINE, ProQuest, EBSCO, ScienceDirect, and Cochrane according to clinical question. The studies were selected based on inclusion and exclusion criteria and led to five useful articles. The selected studies were critically appraised for their validity, importance, and applicability. Results: five cohort studies were found with comparable validity. Only 1 study has accurate relative risk (RR) with 3.97 (1.14 – 13.80) and number needed to harm of 18. Other four studies fulfilled the applicability criteria for our case. Conclusion: the use of FDC anti-tuberculosis therapy increases the risk for tuberculosis recurrence compared with using separate drug formulation.